Parties between thresholds: state subsidies and party behaviour in post-communist democracies - Casal Bertoa, Fernando; Spirova, Maria (SAGE, 2017)
Much has been written about what makes political parties form, persist, change and die. One factor often brought into this discussion is the availability of resources in general and of state financing of political parties in particular. However, an empirical link at the aggregate level is difficult to establish because of various issues of conceptualization, operationalization and measurement. Working at the party level and taking into consideration that state funding provides important resources that make running in elections and achieving a party’s electoral target more likely; this article provides empirical support to the claim that parties who (anticipate to be or) are being funded by the state have a higher chance of forming and surviving in an independent format in the party system. Based on a comparison of 14 post-communist party systems, the main conclusion of the article is that the survival rate for such parties exceeds the survival rate for the non-publicly funded ones in almost all cases. A second, novel and more particular, finding is that parties who find themselves outside parliament, but above the payout threshold, display higher survival rates than parties who are below it.